An estrogen receptor β-selective agonist inhibits non-alcoholic steatohepatitis in preclinical models by regulating bile acid and xenobiotic receptors. Issue 6 (March 2017) - Ponnusamy, Suriyan; Tran, Quynh T; Thiyagarajan, Thirumagal; Miller, Duane D; Bridges, Dave; Narayanan, Ramesh
Non-alcoholic steatohepatitis (NASH) affects 8–10 million people in the US and up to 75% of obese individuals. Despite this, there are no approved oral therapeutics to treat NASH and therefore the need for novel approaches exists. The estrogen receptor β (ER-β)-selective agonist, β-LGND2, inhibits body weight and white adipose tissue, and increases metabolism, resulting in higher energy expenditure and thermogenesis. Due to favorable effects of β-LGND2 on obesity, we hypothesized that β-LGND2 will prevent NASH directly by reducing lipid accumulation in the liver or indirectly by favorably changing body composition. Male C57BL/6 mice fed with high fat diet (HFD) for 10 weeks or methionine choline-deficient diet for four weeks and treated with vehicle exhibited altered liver weights by twofold and increased serum transaminases by 2–6-folds. These changes were not observed in β-LGND2-treated animals. Infiltration of inflammatory cells and collagen deposits, an indication of fibrosis, were observed in the liver of mice fed with HFD for 10 weeks, which were effectively blocked by β-LGND2. Gene expression studies in the liver indicate that pregnane X receptor target genes were significantly increased by HFD, and the increase was inhibited by β-LGND2. On the other hand, metabolomics indicate that bile acid metabolites were significantly increased by β-LGND2. These studies demonstrate that an ER-β agonist might provide therapeutic benefits in NASH by directly modulating the function of xenobiotic and bile acid receptors in the liver, which have important functions in the liver, and indirectly, as demonstrated before, by inhibiting adiposity. Impact statement: Over 75–90% of those classified as clinically obese suffer from co-morbidities, the most common of which is non-alcoholic steatohepatitis (NASH). While there are currently no effective treatment approaches for NASH, data presented here provide preliminary evidence that an estrogen receptor β-selective ligand could have the potential to reduce lipid accumulation and inflammation, and protect liver from NASH.